Nanosized Fluorescent Diagnostic Probes Consisting of Single-domain Antibodies Conjugated with Quantum Dots. (2016) - Sukhanova, Alyona; Even-Desrumeaux, Klervi; Millot, Jean-Marc; Chames, Patrick; Baty, Daniel; Pluot, Michel; Cohen, Jacques H.M.; Nabiev, Igor
Abstract: In state-of-the-art nanoprobes, monoclonal antibodies (mAbs) used as capture molecules are often too large for nanoparticle targeting and are randomly orientated relative to the nanoparticle surface due to the inherent characteristics of the procedure for their fabrication. Here, we are reviewing our recent publications on the smallest known nanoprobes consisting of quantum dots (QDs) and single-domain antibodies (sdAbs), low-molecular-weight fragments of llama immunoglobulins produced in E. coli and attached to the QDs in a strictly specified orientation . The nanoprobe developed has a hydrodynamic diameter smaller than 12 nm and consists of four sdAbs and a QD. They are sensitive and specific enough to accurately estimate even a small number of cells with target biomarkers by means of flow cytometry. The small size of the probes enables immunohistochemical staining much deeper areas of tissue samples as compared to standard probes. Tests with clinical biopsies have shown that sdAb–QD probes provide the same or higher quality of biomarker detection compared to the gold-standard histochemical approach. The nanoprobes developed have many implications for quick multiplexed diagnosis and FRET-based detection platforms.